Drug-resistant tuberculosis: an experience from Qatar. Issue 1 (1st January 2020) - Ali, Maisa; Howady, Faraj; Munir, Waqar; Karim, Hanfa; Al-Suwaidi, Zubaida; Al-Maslamani, Muna; Alkhal, Abdullatif; Elmaki, Nada; Ziglam, Hisham
ABSTRACT: This study was conducted to evaluate the characteristics, treatment outcome and risk factors associated with 223 drug-resistant tuberculosis (DR-TB) cases in the State of Qatar. A descriptive records-based retrospective study was conducted on patients registered at Communicable Disease Centre (CDC), Qatar to all consecutive microbiologically confirmed tuberculosis cases for the period January 2010 – March 2015. Demographic, clinical data, drug-resistance pattern of isolated mycobacteria and treatment outcome was assessed for the patient who completed their treatment in Qatar. Of 3301 patients with positive M. tuberculosis culture were analyzed; 223 (6.7%) were resistant to at least one drug. The overall prevalence of multi-d rug resistant TB (MDR-TB) was 1.2% (n = 38) of patients. A former resident of Indian sub contents was the most common demographic characteristic observed (64.1%). The outcome of treatment was assessed for 85 resistant cases with follow-up after completion of treatment. Cure and relapse rates were 97.6%, and 2.4%, respectively. Drug-resistant TB in Qatar is influenced by migration where the patients were probably infected. Rapid sputum sampling performed in the early stages of the disease, patient isolation, and drug-susceptibility testing should be the standard of care.